RELIGIOUS ACTIVITIES OF THE CHAM PEOPLE IN HO CHI MINH CITY, VIETNAM - Dang Nang Hoa (International Conference on Social and Islamic Studies, 2021)
The Cham ethnic group was one of the first to settle in Saigon - Ho Chi Minh City. TheCham community in Ho Chi Minh City has formed a distinct identity despite the fact thatthe population distribution is far from the original community and, at the same time,under the influence and influence of many other cultural flows. The local charactercontributes to the diversity and richness of Ho Chi Minh City's cultural and humancharacteristics. Economic activities, social organization, and religious activities are themost visible manifestations of this cultural feature. The process of forming the Chamcommunity in Ho Chi Minh City, as well as the characteristics of their religiousactivities, are discussed in this article.